INTEGRITAS SEBAGAI PEMODERASI PENGARUH DUE PROFESSIONAL CARE PADA KINERJA AUDITOR - Ermayanthi, Luh Ayu Alita; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2016)
This study was conducted to determine the effect of due professional care in the performance of the auditor as well as the moderating influence of integrity in the relationship between due professional care in the performance of auditors. Research method used is the quantitative approach associative shape. This research involves all functional positions in the Office of the Inspectorate auditor Klungkung and Gianyar comprised of 34 respondents. This study used a sampling method with saturated or census sampling method. The data analysis technique used is the technique of regression moderation through interaction test. Returns questionnaire in this study were 33. The results showed that the positive effect due professional care in the performance and integrity of auditors able to moderate the influence of due professional care in the performance of auditors in the Office of the Inspectorate Inspectorate Klungkung and Gianyar.
Keywords: Due Professional Care, Integrity, Performance Auditor